Technology portfolio and market value - Jens Schmidt-Ehmcke; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper discusses the impact of a firm's technology portfolio on its market value. Two concepts are used to characterize a firm's portfolio: the number of technological fields and the degree of relatedness within the portfolio characterized by the amount of joint occurrences of patents in technological fields. Based on a theoretical framework using an expanded Tobin's q approach, it presents evidence for a negative influence of portfolio size on the market value caused by a diminishing potential to make use of economies of scale. This discount can be counterbalanced when the relevant fields share a common technological base which is measured by the degree of technological relatedness.
Keywords: L25; O31; O32; 330; technological portfolio; relatedness; patent statistics; tobin's q; economies of scope; Innovationsmanagement; Technologie; Portfolio-Management; Unternehmenswert; Tobin's Q; Patent; Verbundvorteil; Theorie; USA